2013
DOI: 10.1088/0004-637x/764/2/184
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Scaling Relations of Black Hole Masses and Host Galaxy Properties

Abstract: New kinematic data and modeling efforts in the past few years have substantially expanded and revised dynamical measurements of black hole masses (M • ) at the centers of nearby galaxies. Here we compile an updated sample of 72 black holes and their host galaxies, and present revised scaling relations between M • and stellar velocity dispersion (σ), V -band luminosity (L), and bulge stellar mass (M bulge ), for different galaxy subsamples. Our best-fitting power law relations for the full galaxy sample are log… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

124
1,366
6
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,175 publications
(1,499 citation statements)
references
References 127 publications
(137 reference statements)
124
1,366
6
3
Order By: Relevance
“…This "rough scaling" was a premature version of the early correlations between black hole mass, M , BH and host spheroid luminosity, L , sph and also host spheroid mass, M sph (Kormendy & Richstone 1995;Magorrian et al 1998;Marconi & Hunt 2003;Häring & Rix 2004). These initial studies were dominated by high-mass, early-type galaxies, for which they too reported a quasi-linear M M diagrams (Ferrarese & Ford 2005;Graham 2007;Lauer et al 2007a;Gültekin et al 2009;Sani et al 2011;Beifiori et al 2012;Erwin & Gadotti 2012;van den Bosch et al 2012;Vika et al 2012;Kormendy & Ho 2013;McConnell & Ma 2013) continued to use galaxy samples dominated by highmass, early-type systems with M M 0.5 10 , BH 8 ´ and they too recovered a near-linear relation. However, the consensus about a linear M M BH sph -correlation was not unanimous.…”
Section: Introductionmentioning
confidence: 99%
“…This "rough scaling" was a premature version of the early correlations between black hole mass, M , BH and host spheroid luminosity, L , sph and also host spheroid mass, M sph (Kormendy & Richstone 1995;Magorrian et al 1998;Marconi & Hunt 2003;Häring & Rix 2004). These initial studies were dominated by high-mass, early-type galaxies, for which they too reported a quasi-linear M M diagrams (Ferrarese & Ford 2005;Graham 2007;Lauer et al 2007a;Gültekin et al 2009;Sani et al 2011;Beifiori et al 2012;Erwin & Gadotti 2012;van den Bosch et al 2012;Vika et al 2012;Kormendy & Ho 2013;McConnell & Ma 2013) continued to use galaxy samples dominated by highmass, early-type systems with M M 0.5 10 , BH 8 ´ and they too recovered a near-linear relation. However, the consensus about a linear M M BH sph -correlation was not unanimous.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements near the resolution limit can be unreliable, so we conservatively interpret the measurement and its uncertainty to be equivalent to an upper limit of σ = 91 + 48 = 139 km s −1 . Using the M BH -σ relation from McConnell & Ma (2013) implies an upper limit of M BH < 10 7.43 M .…”
Section: A P P E N D I X a : A1 Individual Swift Observationsmentioning
confidence: 99%
“…Boyle & Terlevich 1998;Merloni et al 2004;Aird et al 2010;Madau & Dickinson 2014) and 4) a tight correlation is found between the BH and stellar mass of the host galaxy bulge (e.g. Magorrian et al 1998;McConnell & Ma 2013;Graham & Scott 2013;Kormendy & Ho 2013). There are several examples of composite objects showing both AGN and star formation activity, in the literature (e.g.…”
Section: Introductionmentioning
confidence: 99%